Psychological-Pedagogical and Information Support of Improving the Management Process of General Secondary Schools in the Conditions of Modernization of Education - Taylakov Mukhammad Norbekovich (Researchparks Publishing, 2022)
The article deals with the psychological-pedagogical and information provision of improving the management process of general secondary schools in the conditions of modernization of education.